Practice Patterns of Fenestrated Aortic Aneurysm Repair: Nationwide Comparison of Z-Fen Adoption at Academic and Community Centers Since Commercial Availability. (August 2018) - Wiske, Clay; Lee, Jason T.; Rockman, Caron; Veith, Frank J.; Cayne, Neal; Adelman, Mark; Maldonado, Thomas
Context: Over the past decade, a number of endovascular approaches have evolved to treat aortic aneurysms with anatomy that is not amenable to traditional endovascular repair, although the optimal practice and referral patterns remain in question. The Zenith fenestrated (Z-Fen) endograft (Cook Medical) represents the first commercially available fenestrated graft product in the United States. Objective: We aim to quantify practice patterns in Z-Fen use during the first 5 years of commercial availability, and we identify predictors of high and low uptake. Design, Setting, and Patients: This is a retrospective review of complete order records for Z-Fen endografts since June 2012. We performed univariate and multivariate regressions of predictors that surgeons and centers would be in the top and bottom quartiles of annual Z-Fen use. Results: Since June 15, 2012, 744 surgeons have been trained to use Z-Fen, and 4133 cases have been performed at 409 trained centers. The average annual number of cases per trained surgeon was 4.46 [95% confidence interval (CI), 3.58-5.70]; however, many surgeons performed few or no cases following training, and there was a skew toward users with low average annual volumes (25th percentile 1.23, 50th percentile 2.35, 75th percentile 4.93, and 99th percentile 33.29). Predictors of high annual use in the years following training included academic center (aOR 5.87, P = .001) and training within the first 2 years of availability (aOR 46.23, P < .001). Conclusion: While there is literature supporting the safety and efficacy of Z-Fen, adoption has been relatively slow in an era when the vast majority of vascular surgeons have advanced endovascular skills. Given the training and resources required to use fenestrated or branched aortic endovascular devices, referral patterns should be determined and training should be focused on centers with high expected volumes.